Does economic growth promote electric power consumption? Implications for electricity conservation, expansive, and security policies - Bazán Navarro, Ciro Eduardo (2023)
The purpose of this study is to determine the relationship between electric power consumption per capita (kWh) and real GDP per capita (PEN, constant 2007 prices), in Peru, during the period 1971–2014. The four theoretical hypotheses behind this relationship are the growth hypothesis –electricity consumption explains economic growth–, the conservation hypothesis –economic growth explains electricity consumption–, the feedback hypothesis –mutually affecting explanation between electricity consumption and economic growth–, and neutrality hypothesis –electricity consumption does not explain economic growth and vice versa–. Empirically, we initially conclude that the conservation hypothesis can be confirmed using the Granger Causality test, after estimating the dynamic impacts of the long-run equilibrium and short-run models. We highlight the inelastic behavior of electric power consumption per capita with regard to real GDP per capita. These results have implications for electricity conservation, expansive and security policies. We also discussed investments in electricity generation, transmission and distribution from renewable energy sources such as hydro, wind and solar. These eco-sustainable energies also called green and clean energies, are necessary for the sustainability of the electric power demand and the level of national electrification.